2016
DOI: 10.1016/j.bjm.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium and Aspergillus mycotoxins contaminating wheat silage for dairy cattle feeding in Uruguay

Abstract: Wheat is one of the most important cultivated cereals in Uruguay for human consumption; however, when harvest yields are low, wheat is usually used in ensiling for animal feeding. Ensiling is a forage preservation method that allows for storage during extended periods of time while maintaining nutritional values comparable to fresh pastures. Silage is vulnerable to contamination by spoilage molds and mycotoxins because ensilage materials are excellent substrates for fungal growth. The aim of the study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…del Palacio et al reported lower values for water activity in wheat silage (around 0.70). 32 This could be attributed either to the different silage substrates or the methodology, wherein they evaluated the water activity by calculating the loss of mass after drying. 32 …”
Section: Discussionmentioning
confidence: 99%
“…del Palacio et al reported lower values for water activity in wheat silage (around 0.70). 32 This could be attributed either to the different silage substrates or the methodology, wherein they evaluated the water activity by calculating the loss of mass after drying. 32 …”
Section: Discussionmentioning
confidence: 99%
“…For example, del Palacio et al (2016) demonstrated that 27.5% of these strains produced AFB 1 , 17.5% of them aflatoxin G 2 (AFG 2 ) and 10% synthesized aflatoxin G 1 (AFG 1 ). Interestingly, only 5% of the strains produced AFB 2 (del Palacio et al, 2016). In another study concomitantly performed in Pakistan (Sultana et al, 2017), A. niger, A. flavus, A. fumigatus, A. ochraceous, and A. terrus were identified in both fresh fodder and corn silage.…”
Section: Fungal Activity and Aflatoxin Production In Silagementioning
confidence: 95%
“…The metabolites produced by mushrooms at the time of their growth are major elements in the deterioration of the foodstuffs like the changes of the taste of the food product for example [8,9,10]. They also emerge into serious medical problems, such as the risks of intoxication by mycotoxins [11,12]. Because of its effectiveness and its easy and practical application, the use of the chemical products makes up for the present time the technique most used to fight against the harmful molds [12].…”
Section: Introductionmentioning
confidence: 99%